2014
DOI: 10.1371/journal.pone.0084080
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Single and Concatenated Sets of Mitochondrial Genes at Inferring Metazoan Relationships Relative to Full Mitogenome Data

Abstract: Mitochondrial (mt) genes are some of the most popular and widely-utilized genetic loci in phylogenetic studies of metazoan taxa. However, their linked nature has raised questions on whether using the entire mitogenome for phylogenetics is overkill (at best) or pseudoreplication (at worst). Moreover, no studies have addressed the comparative phylogenetic utility of mitochondrial genes across individual lineages within the entire Metazoa. To comment on the phylogenetic utility of individual mt genes as well as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 60 publications
3
42
0
Order By: Relevance
“…In order to evaluate this in Neotropical catfishes, phylogenetic trees were generated using the three longest mitochondrial genes, which also harbor the majority of informative sites (cox1, nad4 and nad5) and the three mitochondrial genes with the highest performance (nad2, nad4 and nad5), as identified by Havird & Santos [13]. Those trees did not recover the same topology as encountered in the tree recovered using information on the 15 mitochondrial genes (Additional file 6).…”
Section: Resultsmentioning
confidence: 99%
“…In order to evaluate this in Neotropical catfishes, phylogenetic trees were generated using the three longest mitochondrial genes, which also harbor the majority of informative sites (cox1, nad4 and nad5) and the three mitochondrial genes with the highest performance (nad2, nad4 and nad5), as identified by Havird & Santos [13]. Those trees did not recover the same topology as encountered in the tree recovered using information on the 15 mitochondrial genes (Additional file 6).…”
Section: Resultsmentioning
confidence: 99%
“…We can conclude that the genes with more accumulative phylogenetic informativeness are nad5, nad2, nad1, cob and nad6 , while cox1 and cox2 are relatively poor in phylogenetic informativeness despite their prevalence in phylogenetic reconstruction studies. Havird and Santos [30] have recently analysed a large metazoan mitogenomic data set concluding that nad5, nad4 and nad2 genes were the more likely to reproduce the phylogeny obtained from concatenation of all 13 PCGs, while the popular marker cox1 and some of the other long PCGs were the less phylogenetically reliable at this deep taxonomic level. Although particular genes can provide phylogenetic power at distinct divergence time intervals and be more informative in some lineages than others, our data agree with the analysis by [30] in that genes of the NADH dehydrogenase subunits have in general more phylogenetic power than genes coding for the cytochrome subunits.
Figure 4 Metacrangonyctidae mitochondrial protein-coding gene phylogenetic informativeness.
…”
Section: Resultsmentioning
confidence: 99%
“…This discrepancy is most likely attributed to our use of complete mitochondrial genomes that include fourteen protein‐coding genes and two RNAs instead of a single, partial gene ( mtMutS ). There are numerous studies of multiple taxa showing a pattern of incongruent tree topology between single mitochondrial markers and complete mitochondrial genomes despite the fact that they are the same locus and therefore share the same phylogenetic history (Havird & Santos, ; Knaus et al, ; Luo et al, ; Nadimi et al, ; Pacheco et al, ; Rohland et al, ; Urantowka et al, ; Wang et al, ; Willerslev et al, ). For example, Havird, Santos Scott, and Schierwater, () analyze the performance of single and concatenated sets of mitochondrial genes relative to complete mitochondrial genomes for phylogenetic reconstruction of metazoans.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Havird, Santos Scott, and Schierwater, () analyze the performance of single and concatenated sets of mitochondrial genes relative to complete mitochondrial genomes for phylogenetic reconstruction of metazoans. Their findings show that single genes are not able to reproduce the topology of a mitogenomic phylogeny (Havird & Santos, ). A similar study, but focusing on birds, showed that single mitochondrial genes resulted in incorrect and contradictory phylogenetic relationships, while the use of complete mitochondrial genomes accurately reflected the species tree (Urantowka et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation